ROBOTIC PROCESS AUTOMATION FOR QUALITY CONTROL ASSESSMENT USING SELENIUM - Refgiufi Patria Avrianto; Mochamad Isnin Faried; Erick Dazki; Richardus Eko Indrajit (Informatika, Universitas Jenderal Soedirman, 2022)
Robotic Process Automation (RPA) is a form of technology to automate tasks and routines performed by humans, which can be instructed to machine. Along with the rapid development of technology, the time that can be used to maintain the quality of a technology is becoming increasingly narrow. Therefore, RPA will imitate activities or tasks performed by humans on a computer with a much faster processing time and 100% accuracy without